Correlates of Occupational Heat-Induced Illness Costs: Case Study of South Australia 2000 to 2014. Issue 9 (September 2018) - Xiang, Jianjun; Hansen, Alana; Pisaniello, Dino; Dear, Keith; Bi, Peng
Abstract : Objective: To investigate the profile of occupational heat-induced illness costs in South Australia and to examine the association with high temperature. Methods: Workers' compensation claim data were used to quantify the associations between maximum temperature ( T max ) and occupational heat illness (OHI)-related costs, using time-series analysis after controlling for confounding factors. Results: Four hundred thirty-eight OHI claims in 2000 to 2014 resulted in total medical costs of AU6, 002, 840 and 5, 036 work days lost. Relatively higher OHI burdens were found in men, those aged 25 to 44 years, new workers, medium-size businesses, and those employed in the mining industry. A 1 °C increase in T max above about 33 °C was associated with a 41.6% increase in medical costs and a 74.8% increase in days lost due to OHI, respectively. Conclusions: The cost profile of OHI may be used to justify interventions for particular industries, occupations, and worker categories. Abstract : Supplemental Digital Content is available in the text